Sporulation, Heat Resistance, and Biological Properties of Clostridium perfringens - Nishida, S. (1969)
A sporulation medium for 134 Clostridium perfringens strains, including types A, B, C, D, E, and F, was devised according to Grelet's observation that sporulation occurred when cultural environment became limited in any nutritional requirement indispensable for the growth of the organism. Sporulation took place most prominently when 10% cooked-meat broth (pH 7.2) containing 3% Proteose Peptone and 1% glucose was used for the preculture and 2% Poli Peptone medium (pH 7.8) was used for the subculture medium. Sometimes, terminal spores could be observed. A correlation between sporulation and heat resistance was examined by use of C. perfringens strains isolated from samples heated at different temperatures. Almost all strains isolated from unheated samples and from those heated at lower temperatures gave rise to spores in our sporulation medium, but the spores were weakly heat-resistant, whereas strains isolated from samples heated at 100 C for 60 min were highly heat-resistant but sporulated poorly. A majority of these heat-resistant strains were non-gelatinolytic and definitely salicin-fermenting.